Tsc Gene Locus Disruption and Differences in Renal Epithelial Extracellular Vesicles - Kumar, Prashant; Zadjali, Fahad; Yao, Ying; Siroky, Brian; Astrinidis, Aristotelis; Gross, Kenneth W.; Bissler, John J. (Frontiers in Physiology, 2021)
In tuberous sclerosis complex (TSC), Tsc2 mutations are associated with more severe disease manifestations than Tsc1 mutations and the role of extracellular vesicles (EVs) in this context is not yet studied. We report a comparative analysis of EVs derived from isogenic renal cells except for Tsc1 or Tsc2 gene status and hypothesized that in spite of having similar physical characteristics, EVs modulate signaling pathways differently, thus leading to TSC heterogenicity. We used mouse inner medullary collecting duct (mIMCD3) cells with the Tsc1 (T1G cells) or Tsc2 (T2J cells) gene disrupted by CRISPR/CAS9. EVs were isolated from the cell culture media by size-exclusion column chromatography followed by detailed physical and chemical characterization. Physical characterization of EVs was accessed by tunable resistive pulse sensing and dynamic light scattering, revealing similar average sizes and zeta potentials (at pH 7.4) for EVs from mIMCD3 (123.5 ± 5.7 nm and −16.3 ± 2.1 mV), T1G cells (131.5 ± 8.3 nm and −19.8 ± 2.7 mV), and T2J cells (127.3 ± 4.9 nm and −20.2 ± 2.1 mV). EVs derived from parental mIMCD3 cells and both mutated cell lines were heterogeneous (>90% of EVs < 150 nm) in nature. Immunoblotting detected cilial Hedgehog signaling protein Arl13b; intercellular proteins TSG101 and Alix; and transmembrane proteins CD63, CD9, and CD81. Compared to Tsc2 deletion, Tsc1 deletion cells had reduced EV production and release rates. EVs from Tsc1 mutant cells altered mTORC1, autophagy, and β-catenin pathways differently than EVs from Tsc2-mutated cells. Quantitative PCR analysis revealed the down regulation of miR-212a-3p and miR-99a-5p in EVs from Tsc2-mutated cells compared to EVs from Tsc1-mutant cells. Thus, EV-derived miR-212-3p and mIR-99a-5p axes may represent therapeutic targets or biomarkers for TSC disease.